2012
DOI: 10.1007/s10549-012-2310-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of breast density with breast cancer mortality in African American and white women screened in community practice

Abstract: The effect of breast density on survival outcomes for American women who participate in screening remains unknown. We studied the role of breast density on both breast cancer and other cause of mortality in screened women. Data for women with breast cancer, identified from the community-based Carolina Mammography Registry, were linked with the North Carolina cancer registry and NC death tapes for this study. Cause-specific Cox proportional hazards models were developed to analyze the effect of several covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…14,21,24,[27][28][29] Breast density has also been associated with an increased risk of local and locoregional recurrence of breast cancer but not distant metastasis or survival. 30,31 This finding is consistent with 2 recent large studies that found that breast density was not associated with increased breast cancer mortality or all-cause mortality rates 32,33 ; however, additional research is needed because of the limited studies on this topic. Breast density decreases with advancing age; a large study found that 74% of women in their 40s had dense breasts (D3 or D4) as compared with 36% of women in their 70s.…”
Section: High Breast Density Increases Breast Cancer Risksupporting
confidence: 85%
“…14,21,24,[27][28][29] Breast density has also been associated with an increased risk of local and locoregional recurrence of breast cancer but not distant metastasis or survival. 30,31 This finding is consistent with 2 recent large studies that found that breast density was not associated with increased breast cancer mortality or all-cause mortality rates 32,33 ; however, additional research is needed because of the limited studies on this topic. Breast density decreases with advancing age; a large study found that 74% of women in their 40s had dense breasts (D3 or D4) as compared with 36% of women in their 70s.…”
Section: High Breast Density Increases Breast Cancer Risksupporting
confidence: 85%
“…In contrast, Chiu et al [37] reported significant increased mortality from breast cancer among women with greater dense tissue, however, breast tissue was broadly categorized as “dense” or “nondense”. Our results vary from studies of breast cancer cases that found null associations between breast density and mortality, however these studies incompletely adjusted for confounders of prognosis such as comorbidities, treatment, tumor size or stage of cancer [19,20,38]. …”
Section: Discussioncontrasting
confidence: 89%
“…In the present study, breast volume in relation to breast cancer prognosis was assessed rather than mammographic density. While mammographic density is a strong risk factor for breast cancer, its impact on breast cancer prognosis is unclear . Women with large breasts are more likely to have a decreased mammographic density, and mammographic density seems to be less of a breast cancer risk factor for women with larger breasts .…”
Section: Discussionmentioning
confidence: 99%
“…While mammographic density is a strong risk factor for breast cancer, its impact on breast cancer prognosis is unclear. 48 Women with large breasts are more likely to have a decreased mammographic density, and mammographic density seems to be less of a breast cancer risk factor for women with larger breasts. 19 Dense matter in large breasts may be constitutionally different from that in smaller breasts.…”
Section: Discussionmentioning
confidence: 99%